Governans untuk Geopark: Langkawi Geopark sebagai acuan - Halimaton Saadiah Hashim; Sarah Aziz Abdul; Rahimah Abdul Aziz.; Ghani Aziz; Chan, Kim Ling@Geraldine (Universiti Kebangsaan Malaysia, 2010)
Langkawi Islands have gone through many changes since it changed status from being ‘Mahsuri Legendary Island’ and ‘Langkawi 99 Magical Islands’ to ‘Langkawi Tax Free Island’ (1987) to ‘Langkawi Tourism City’ (2000). Its recognition as ‘Langkawi Geopark (2007) has put it on an international arena. The main question is whether Langkawi’s existing management system meets the requirements to implement the geopark concept effectively? Is the current governance system still relevant and what are the neccessary changes? What is the governance system that is needed towards sustainable development? This article discusses the formulation of a governance system for Langkawi Geopark which contains the main characteristics for conservation (geological, biological and cultural heritage); development and provision of tourism infrastructure (hotels/tourist resorts, education, exhibition, recreation and public awareness); and socio-economic development (economic activities, local community participation and new opportunities). The formulation of geopark’s management and governance system requires the understanding of concepts of geopark, heritage and heritage conservation, governance and governance for sustainable development, transition management and critical elements in the current management system. The desired concept has not been formed. However, in general the current practice can continue but with systematic adapation and improvements in awareness building acitivities through public education programme, that is comprehensive, more consultative programmes, and decision-making processes that involve the stakeholders.